LEGAL ASPECTS OF ISLAMIC BANKING AND FINANCE IN NIGERIA - Alkali, Muhammad Bashir; Buang, Ahmad Hidayat (Jurnal Syariah, 2017)
Whether or not they are considered spiritual or mundane, laws which govern every aspect of human affairs in Nigeria, especially in regards to Islamic Banking and Financial institutions, exist owing to the plural legal system in the country, these aspects of society are regulated by both the Islamic and statutory laws imposed by the former British colonizers. Various legal sources, including the Qur’ān, the ḥadīth, constitution, Banks and Other Financial Institutions Act, Central Bank Act, and Nigerian Deposits Insurance Corporation Act constitute its regulatory framework. This work intends to analyze the said laws with the objective of identifying and filling the lacunae therein, in order to forestall future legal obstacles to the system. This study therefore analyses this convoluted legal hybridity and suggests ways of overcoming any obstacles. The methodology utilized in this research is that of literature review. This study concludes with the suggestion that the said obstacles may be overcome through more emphasis on the use of religious legislation, amendments to the constitution, and a new legislation.